2010
DOI: 10.1007/s00439-009-0781-z
|View full text |Cite
|
Sign up to set email alerts
|

PD1 as a common candidate susceptibility gene of subacute sclerosing panencephalitis

Abstract: Although the exact pathogenesis of subacute sclerosing panencephalitis (SSPE) remains to be determined, our previous data suggested a genetic contribution to the host susceptibility to SSPE. During chronic viral infection, virus-specific cytotoxic T lymphocytes display poor effector functions. Since co-inhibitory molecules are involved in the suppression of T lymphocytes, we investigated whether single nucleotide polymorphisms (SNPs) of genes encoding co-inhibitory molecules contributed to a susceptibility to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 39 publications
2
51
0
2
Order By: Relevance
“…One recent report demonstrated a significant association of PD-1.1 SNP and the expression levels of PD-1 with subacute sclerosing panencephalitis (SSPE) in Japanese and Filipinos population [36]. We showed a significant association of PD-1.6 SNP rather than PD-1.1 SNP with chronic HBV infection in Chinese population.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…One recent report demonstrated a significant association of PD-1.1 SNP and the expression levels of PD-1 with subacute sclerosing panencephalitis (SSPE) in Japanese and Filipinos population [36]. We showed a significant association of PD-1.6 SNP rather than PD-1.1 SNP with chronic HBV infection in Chinese population.…”
Section: Discussionmentioning
confidence: 67%
“…The PD-1.6 SNPs with G allele, which showed lower frequencies in chronic HBV infection, may be involved in the downregulation of PD-1 expression in the T cells associated with the immune responses, including T-cell activation and the production of antiviral cytokines, such as interferon-␥ and tumor necrosis factor, via so far unknown mechanism in chronic HBV infection, conferring a protective effect. Recently, it has been demonstrated that the promoter activity in the construct with Ϫ606A allele was significantly lower than that with Ϫ606G allele [36]. In our study, the combination of PD-1.6 genotype containing G allele (GA or GG) with the PD-1.1 GG genotype decreased the OR from 0.667 to 0.381 and the PD-1 haplotype comprising PD-1.6 G and PD-1.1 G alleles decreased the OR from 0.662 in PD-1.6 G allele to 0.530.…”
Section: Discussionmentioning
confidence: 98%
“…This -606 G/A single-nucleotide polymorphism (SNP) resides in the putative binding site for UCE-2 transcription regulators (GGCCG at position -610 to -606). A haplotype of the -606 G allele with a high promoter activity was correlated with the development of SSPE (15). The relative PD-1 expression was higher in SSPE patients compared to the control (15), however, the correlation between this Asian-specific PD-1 SNP and NSCLC has not been well investigated.…”
Section: Pd-1 Gene Promoter Polymorphisms Correlate With a Poor Prognmentioning
confidence: 99%
“…The PD-1 -606 G allele at the promoter showed a significant correlation with Japanese subacute sclerosing panencephalitis (SSPE) (15). This -606 G/A single-nucleotide polymorphism (SNP) resides in the putative binding site for UCE-2 transcription regulators (GGCCG at position -610 to -606).…”
Section: Pd-1 Gene Promoter Polymorphisms Correlate With a Poor Prognmentioning
confidence: 99%
See 1 more Smart Citation